The Sectarian Ideology of the Islamic Online Media in Indonesia - Moch. Syarif Hidayatullah (Faculty of Adab and Humanities, Syarif Hidayatullah State Islamic University of Jakarta., 2017)
Numerous Islamic groups in Indonesia use the internet to offer ideology against other groups or other sects to internet users. This study focuses on sectarian ideology on Islamic online media in Indonesia. Having combined and sought this media, I found that lppimakassar.com and manhajsala- fi.com are the most intensive sites in offering sectarian ideology. This study aims to examine the ideological identity and pattern of the websites linked to the administrators or writers of the web- sites. To find their ideology, this article uses topic headings, news, and articles to analyze. This meth- od has led me to find two Islamic online media: lppimakassar.com and manhajsalafi.com. The former is affiliated to the Salafi group while the latter to the Aswaja group. These two websites adopt their thoughts abroad.DOI: 10.15408/insaniyat.v1i2.5468